Biodegradation - Bouwer, Edward; Gunsch, Claudia K.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
...Online submission and review system now available!... Biodegradation publishes papers, reviews, and mini-reviews on all aspects of science pertaining to the biotransformation, mineralization, detoxification, recycling, amelioration or treatment of chemicals or waste materials by naturally-occurring microbial strains, microbial associations, or recombinant organisms. Submissions of manuscripts describing fundamental studies and novel discoveries are highly encouraged. Biodegradation does not publish routine case studies or results of biotreatment demonstrations that do not present new concepts or novel observations. Areas of particular interest include: - biochemistry of biodegradative pathways; - genetics of biodegradative organisms and the development of recombinant biodegrading organisms; - molecular biology-based studies of biodegradative microbial communities, including metagenomic approaches (examinations of whole-community genomes); - enhancement of naturally-occurring biodegradative properties and activities; - novel applications of biodegradation and biotransformation technology, e.g. to soil, water, sewage, heavy metals and radionuclides, organohalogens, high-COD wastes, straight-, branched-chain and aromatic hydrocarbons; - modelling and scale-up of laboratory processes and design of bioreactor systems; - economic and legal aspects of biological treatment of waste.
Keywords: Geochemistry; Microbiology; Soil science; Soil conservation; Waste management; Environmental pollution; Water pollution; Microbiology; Soil Science & Conservation; Geochemistry; Terrestrial Pollution; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Waste Management/Waste Technology